Exploring the impact of a life education program on the resilience of nursing students. - Yao-Mei Chuang; Wei-Hsiang Huang (PLoS ONE)
This study explores the impact of a life education program on nursing students' psychological resilience, focusing on meaning in life, life attitudes, and positive psychology. A quasi-experimental design with pre- and post-tests was used, involving 87 nursing students (40 in the experimental group, 47 in the control group) aged 20-25 years, with 85% being female. The experimental group attended a five-week life education program (500 minutes total). The Purpose in Life Test, Life Attitude Scale, and Positive Mental Health Scale were used as measurement tools, and data were analyzed using Generalized Estimating Equations (GEE). The results showed significant interaction effects in the experimental group on meaning in life (B = 4.09, p < 0.001), life attitudes (B = 11.29, p < 0.001), and positive psychology (B = 4.81, p = 0.009). Paired t-tests further confirmed significant within-group improvements, while the control group showed no changes. This study recommends integrating life education into nursing curricula and providing teacher training to enhance course delivery. Collaboration with mental health organizations is also suggested to offer additional support. Future research should expand the sample and explore qualitative methods to deepen understanding of life education's impact.